OC-068 Albumin is central in mediating the cardio-renal dysfunction of cirrhosis: a study in analbuminaemic rats. (28th May 2012) - Martinez, R Garcia; Habtesion, A; Tritto, G; Jover, M; Jalan, R; Davies, N
Abstract : Introduction: Albumin is a multifunctional protein which is reduced in concentration and function in liver disease. Albumin infusion prevents and improves renal dysfunction in patients with advanced liver failure but the mechanisms of its beneficial properties are unclear. We hypothesised that albumin is central in the maintenance of cardio-renal function in cirrhosis and albumin impairment worsens outcome. In order to answer this question we investigated analbuminaemic rats, characterised by lack of albumin but with normal protein concentration, following induction of cirrhosis with bile duct ligation (BDL). Methods: Male Sprague-Dawley (SD) and Nagase analbuminaemic (NAR) rats were studied 6 weeks after BDL or sham surgery (n=6 sham-SD, 8 sham-NAR, 7 SD-BDL, 7 NAR-BDL). Rats underwent systemic mean arterial pressure (MAP) and portal pressure (PP) assessment under terminal anaesthesia. Plasma and urine were collected for measurements of renal function and protein profile. Plasma renin activity (PRA) was measured as a marker of cardio-renal dysfunction. Urinary neopterin, a marker of macrophage activation was assessed. Results: NARs showed plasma total protein concentration similar to SD despite lack of albumin before (72±15 vs 82±8) and after BDL (67±7 vs 75±22). After BDL both groups of animals showed histological evidence of severe liver damage, though the NARs showed a significantly worse systemic haemodynamics with lower MAP (p=0.01), evidence of renal dysfunction indicated by higher plasma creatinine and higher PRA (p<0.05) compared with SD (Abstract OC-068 figure 1 ). There was a significant inflammatory response following BDL in both groups showed by an increase in urinary neopterin which was found to correlate with PRA (r=0.59, p<0.01). Conclusion: A lack of albumin was associated with a raised PRA and a marked deterioration in systemic haemodynamics and renal function after liver injury (BDL), despite normal total plasma protein concentration. This worsened outcome in the absence of albumin strongly supports the central role of albumin in maintenance of cardio-renal function in liver failure and may indicate that albumin plays a crucial role in moderating inflammation. Competing interests: None declared.